2023
DOI: 10.1212/con.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Central Nervous System Autoimmune, Paraneoplastic, and Neuro-rheumatologic Disorders

Abstract: OBJECTIVE: This article provides an overview of the imaging modalities used in the evaluation of central nervous system (CNS) autoimmune, paraneoplastic, and neuro-rheumatologic disorders. An approach is outlined for interpreting imaging findings in this context, synthesizing a differential diagnosis based on certain imaging patterns, and choosing further imaging for specific diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…A comprehensive overview of paraneoplastic syndromes is beyond the scope of this review and can be found in other Continuum issues. 66,67 COMMENT This case illustrates how cardiac function can be affected in a patient with a brain tumor infiltrating the right insula. Lack of clinical improvement despite treatment with corticosteroids and no electrographic findings to suggest an epileptiform mechanism for the events led to selection of a cardiac pacemaker as the appropriate treatment in this case.…”
Section: Case 11-2mentioning
confidence: 98%
See 1 more Smart Citation
“…A comprehensive overview of paraneoplastic syndromes is beyond the scope of this review and can be found in other Continuum issues. 66,67 COMMENT This case illustrates how cardiac function can be affected in a patient with a brain tumor infiltrating the right insula. Lack of clinical improvement despite treatment with corticosteroids and no electrographic findings to suggest an epileptiform mechanism for the events led to selection of a cardiac pacemaker as the appropriate treatment in this case.…”
Section: Case 11-2mentioning
confidence: 98%
“…Although supportive treatment is similar regardless of the etiology, distinguishing between neurotoxicity from antineoplastic agents (eg, checkpoint inhibitors) and antibody-mediated conditions is key for appropriately choosing targeted therapies, which often comprise tumor-related treatment and immunosuppression. A comprehensive overview of paraneoplastic syndromes is beyond the scope of this review and can be found in other Continuum issues 66,67 …”
Section: Indirect Tumor-mediated Complicationsmentioning
confidence: 99%
“…It may appear serpentine as it follows the sulci where it must be carefully distinguished from blood vessels which also appear hyperintense when filled with contrast. Care should also be taken to look at the noncontrasted T1 sequence to distinguish from other causes of T1 hyperintense signal in the leptomeninges such as methemoglobin (subarachnoid hemorrhage) or melanin from metastatic melanoma [ 109 ••]. A pathognomonic finding in the spinal cord is the “Trident Sign” with a characteristic dorsal subpial pattern of enhancement [ 110 ].…”
Section: Neuroimaging Findingsmentioning
confidence: 99%